Die huwelik as ‘instelling van God’ (met implikasies vir gay huwelike) - De Villiers, G. (Verbum et ecclesia, 2007)
This article focuses on marriage. It appears that marriage is in the first place a social cultural institution with legal implications, and not religious by nature. Concepts and practices regarding marriage change along with social and cultural movements. Regarding the twenty first century, a marked shift from patriarchy towards equality has been observed. Marriage practices have changed: the man is no longer sole breadwinner and head of the household, the woman no longer only the pleasing wife and mother to his children. Simultaneously gay relationships are becoming part of social reality. Gay couples express a wish for their relationships to be acknowledged by religious institutions. What does the Bible say? Marriage as ‘ordained’ by God has no biblical foundation, especially not according to the traditionally quoted Genesis 2:18. In the twenty first century the concepts ‘marriage, relationship, sin, sexuality and sex’ need to be revised in order to comply with the biblical demand of love.